Evaluation of Basic Government Service Capability in Chinese Cities
X, 243 p. 91 illus.
Keywords: This book reports on the results of a survey of 38 major Chinese cities’ public service performances and provides an overview of the development of basic public services in the larger cities. The quality of urban public services is examined from 9 different perspectives: basic healthcare and public health, housing, public transportation, public security, employment and social security, compulsory education, urban environment, culture and sports, and government services. Moreover, a series of indices are applied to further study the degree of public satisfaction with basic public services in these cities. These indices include the index of GDP leveraging satisfaction with basic public services, the rising index of satisfaction with basic public services in cities, and the development index of satisfaction with the basic public service elements. On the basis of the survey results, this book also identifies the most important social issues among the surveyed public, including food anddrinking water safety, information security, housing prices, pensions, and air and environment quality.